Identification of metabolic signatures associated with anti-inflammatory effects of Pheonix dactylifera L. using NMR and MS-based metabolomics - Abdul Hamid, Nur Ashikin (2019)
Phoenix dactylifera L. (date palm) is an essential agricultural crop in most arid regions of the world and have been used in traditional medicine to treat illnesses. The extracts of P. dactylifera pulps and seeds are reported to possess valuable pharmacological attributes including antioxidant, anti-fungal and anti-inflammatory activity. However, there is still a lack of scientific data to support the potency of P. dactylifera in treating inflammation. Thus, the primary purpose of this study is to fill in the current research gap concerning the mechanism underlying the anti-inflammatory effects of this fruit crops. There are many date varieties available in the market with various phenotypic features, consumers’ preferences and price ranges. Eighteen varieties of dates from two date producing countries were selected including Algerian Lahmira (LM), Timjouhert (TM), Adham Talmine (AT), Deglet Talmine (DT), Adam Boullah (AB), Tinasser (TN), Deglet (DG), Deglet Nour (DN) and Takerbouch (TB) along with Saudi varieties of Berni (BR), Halaoua (HL), Shalabi (SB), Sogaai (SG), Sukkari (SK), Nebtat Ali (NB), Anbara (AN), Ajwa (AJ) and Medjoul (MJ). The quality was evaluated based on the metabolite composition, physico-chemical characteristics and biological activities which include nitric oxide (NO) inhibition via the cell-based approach and NO scavenging abilities. The correlation between the phytochemicals and biological activities was achieved via ¹H nuclear magnetic resonance (NMR) based metabolomics approach. Algerian Deglet and Saudi Ajwa showed the most promising NO inhibition as compared to the rest of date varieties. The current study was then focusing on the variation in phytochemicals and biological activities between the seeds and pulps of P. dactylifera. The information on chemical constituents was further strengthen utilizing ultra-high performance liquid chromatography mass spectrometry (UHPLC-MS) technique. The multi-platforms metabolomics of MS and NMR methods were adopted in exploring differences between the phytochemical in seed and pulp extracts. The seed of Algerian Deglet revealed a significantly lower IC50 values of NO inhibitory and DPPH scavenging with the IC50 values of 107.99 µg/mL and 12.58 µg/mL, respectively. Among the metabolites that prominently contributed towards the observed bioactivities as suggested by Partial Least Squares analysis including catechin, ascorbic acid and serine. The proposed metabolic pathway indicated the higher amount of several metabolites in date seeds as compared to the pulps. The variation between the extracellular metabolites of RAW 264.7 cells from different passage numbers was determined along with the impact of different harvesting protocols on the intracellular metabolites. The trypsinized RAW cells from lower passage groups gave higher intensities of several metabolites including asparagine, serine and tryptophan. The Principal Component Analysis revealed variation between cells from different passage and harvesting methods as indicated by the formation of clusters in the score plot. The current study is the first to report on the passage and harvesting dependent effects using metabolomics workflow for the murine macrophage, RAW 264.7 cells. The overall bio-markers from the cell metabolome of the induced and treated cells and also bio-active compounds in date extracts linking to the anti-inflammatory property was obtained in the present study. The acquired data adds up to the existing knowledge on anti-inflammatory effects of date seed extracts by highlighting their capacity to assist the inversion of activated RAW 264.7 cells back to the normal state. This work demonstrated the potential application of metabolomics approaches as tools in evaluating quality of plant materials and also in providing better insight into cells biology.